FOXD2-AS1 Predicts Dismal Prognosis for Oral Squamous Cell Carcinoma and Regulates Cell Proliferation. (22nd October 2020) - Liang, Xiaowei; Chen, Zhizhao; Wu, Geng
The roles of long noncoding RNA FOXD2 adjacent opposite strand RNA 1 (FOXD2-AS1) in oral squamous cell carcinoma (OSCC) remain largely unknown. Here, the Atlas of Noncoding RNAs in Cancer online database was utilized to analyze the expression and clinical significance of FOXD2-AS1 in OSCC. Then, the cell proliferation of FOXD2-AS1-silenced OSCC cells (CAL-27) was assessed by MTT and clone formation experiments. FOXD2-AS1-coexpressed genes were enriched and analyzed via circlncRNAnet and Metascape tools. Finally, key molecules of the signal pathways of the aforementioned coexpressed genes were verified by western blotting. We found that FOXD2-AS1 was significantly highly expressed in OSCC tissues, and correlated with poor pathological grade and prognosis in patients with OSCC. Cell viability and clone formation ability were significantly inhibited after the knockdown of FOXD2-AS1. A total of 32 coexpressed genes of FOXD2-AS1 were identified, and those genes were enriched in the cell cycle. In conclusion, FOXD2-AS1 may be served as a potential prognostic indicator and therapeutic target for OSCC.